The Calcium Channel Blocker Gabapentin, a Benchmark Drug in Pain Studies, Inhibits Translocation of the Epsilon Isoform of Protein Kinase C in Cultured Nociceptors: A Novel Mechanism of Action - Vittorio Vellani; Chiara Giacomoni (New Ideas Concerning Science and Technology Vol. 4, 2021)
Gabapentin is a well-established anticonvulsant drug which is also effective for the treatment of neuropathic pain. Gabapentin, a structural analogue of the inhibitory neurotransmitter gamma-aminobutyric acid, was originally developed in the early nineties as a third-generation antiepileptic drug. Although the exact mechanism leading to relief of allodynia and hyperalgesia caused by neuropathy is not known, the blocking effect of gabapentin on voltage-dependent calcium channels has been proposed to be involved. In order to further evaluate its analgesic mechanisms, we tested the efficacy of gabapentin on translocation of protein kinase C epsilon (PKC????) in cultured peripheral neurons isolated from rat dorsal root ganglia (DRGs). We found that gabapentin significantly reduced PKC???? translocation induced by the pronociceptive peptides bradykinin and prokineticin 2, which are involved in both inflammatory and chronic pain. We recently showed that paracetamol (acetaminophen), a very commonly used analgesic drug, also produces inhibition of PKC????. We tested the effect of the combined use of paracetamol and gabapentin, and we found that the inhibition of translocation adds up in a non-cooperative fashion. Our study provides a novel mechanism of action for gabapentin in sensory neurons and suggests a rationale and a mechanism of action for the combined use of paracetamol and gabapentin, which has recently been shown to be effective, with a cumulative behavior, in the control of postoperative pain in human patients.